Molecular mechanisms of the Guizhi decoction on osteoarthritis based on an integrated network pharmacology and RNA sequencing approach with experimental validation - Chen, Yan; Xue, Yan; Wang, Xuezong; Jiang, Ding; Xu, Qinguang; Wang, Lin; Zheng, Yuxin; Shi, Ying; Cao, Yuelong (Frontiers in Genetics, 2023)
Background: Our aim was to determine the potential pharmacological mechanisms of the Guizhi decoction (GZD) in the treatment of osteoarthritis (OA) through an integrated approach of network pharmacological analyses, RNA sequencing (RNA-seq), and experimental validation. Methods: The quality control and identification of bioactive compounds of the GZD were carried out by using ultra-performance liquid chromatography (UPLC), and their OA-related genes were identified through overlapping traditional Chinese medicine systems pharmacology database (TCMSP), DrugBank and SEA Search Server databases, and GeneCards. The Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis were implemented after constructing the component–target network. RNA-seq was used to screen differentially expressed genes (DEGs) under intervention conditions with and without the GZD in vitro. The crossover signaling pathways between RNA-seq and network pharmacology were then analyzed. Accordingly, protein–protein interaction (PPI) networks, GO, and KEGG analysis were performed using the Cytoscape, STRING, or DAVID database. The OA rat model was established to further verify the pharmacological effects in vivo. Hematoxylin–eosin (H&E) and safranin O/fast green (S-O) staining were used to grade the histopathological features of the cartilage. We verified the mRNA and protein expressions of the key targets related to the TNF signaling pathways in vivo and in vitro by qPCR, Western blotting (WB), and immunofluorescence assay. In addition, we also detected inflammatory cytokines in the rat serum by Luminex liquid suspension chip, which included tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and interleukin-1β (IL-1β). Results: Eighteen compounds and 373 targets of the GZD were identified. A total of 2,356 OA-related genes were obtained from the GeneCards database. A total of three hub active ingredients of quercetin, kaempferol, and beta-sitosterol were determined, while 166 target genes associated with OA were finally overlapped. The RNA-seq analysis revealed 1,426 DEGs. In the KEGG intersection between network pharmacology and RNA-seq analysis, the closest screening relevant to GZD treatment was the TNF signaling pathway, of which TNF, IL-6, and IL-1β were classified as hub genes. In consistent, H&E and S-O staining of the rat model showed that GZD could attenuate cartilage degradation. When compared with the OA group in vivo and in vitro, the mRNA levels of TNF-α, IL-1β, IL-6, matrix metalloproteinase 3 (MMP3), and matrix metalloproteinase 9 (MMP9) were all downregulated in the GZD group (all p < 0.05). The expression levels of anabolic proteins (Col2α1 and SOX9) were all higher in the GZD group than in the OA group (p < 0.05), while the expression levels of the catabolic proteins (MMP9 and COX-2) and TNF-α in the GZD group were significantly lower than those in the OA group (p < 0.05). In addition, the expression levels of TNF, IL-6, and IL-1β were upregulated in the OA group, while the GZD group prevented such aberrations (p < 0.01). Conclusion: The present study reveals that the mechanism of the GZD against OA may be related to the regulation of the TNF signaling pathway and inhibition of inflammatory response.